Lead-lag dynamics of a rotor with stick-slip nonlinearity - Andersch, P.; Hajek, M. (My University, 2015)
An assessment of a frictional helicopter blade attachment with regard to its influence on the dynamics of the in-plane blade motion is presented. For detailed system analysis, a 3D finite element model with contact modeling has been created and validated using preexisting test data. Using the insights gained from 3D finite element simulations, a reduced order model suitable for dynamical simulations is derived and parameterized. Eventually, the reduced order model for the blade attachment is inserted into a hingeless dynamical rotor model with elastic coupling. The influence of the blade attachment on lead-lag dynamic behavior is investigated using the developed model and multiple configurations are compared to each other to identify the effects of the nonlinear blade attachment model on lead-lag frequency and damping ratio as well as elastic coupling prevalent in the hingeless rotor configuration
Keywords: Dynamics